Estimasi Cadangan dan Desain Tambang Nikel Laterit Menggunakan Software Surpac Pada PT. Hikari Jeindo Kabupaten Konawe Utara Sulawesi Tenggara - Asliadi, Amril; Rembah, Rina; Nurfasiha, Nurfasiha (Program Studi Teknik Pertambangan, Fakultas Teknik, Universitas Sulawesi Tenggara, 2024)
Hikari Jeindo is a private company engaged in nickel mining with its head office in the city of Kendari, Southeast Sulawesi and a mining location in the Langgikima sub-district. North Konawe Regency. This research was carried out in block 4 with a block area of ​​48 hectares. For the IUP area of ​​PT. Hikari Jeindo has an IUP area of ​​177.70 Ha. In this research, the problem is how to design a laterite nickel deposit pit in the research area using the Inverse Distance Weight (IDW) method and what the volume and tonnage of reserves should be. The aim of this research is to create a pit design for laterite nickel deposits in the research area and to estimate the volume and tonnage of reserves in the research area The research results obtained during the final assignment research at PT. Hikari Jeindo in block 4 where a pit design is carried out which functions to limit the mining block that will be carried out, with a pit opening area of ​​48 Ha. Where the height of the ladder is 5 m, the width of the ladder is 2.5 m and the slope of the ladder is 45%. Estimations were carried out with the help of Surpac 6.3 software by using the method and what was obtained was a volume of 258,593 m3 with a tonnage of 387,890 m3/ton with an average Ni content of 1.82% and Fe 11.18%.